Online and Offline Performance Gains Following Motor Imagery Practice: A Comprehensive Review of Behavioral and Neuroimaging Studies - Di Rienzo, Franck; Debarnot, Ursula; Daligault, Sébastien; Saruco, Elodie; Delpuech, Claude; Doyon, Julien; Collet, Christian; Guillot, Aymeric (Frontiers in Human Neuroscience, 2016)
There is now compelling evidence that motor imagery (MI) promotes motor learning. While MI has been shown to influence the early stages of the learning process, recent data revealed that sleep also contributes to the consolidation of the memory trace. How such “online” and “offline” processes take place and how they interact to impact the neural underpinnings of movements has received little attention. The aim of the present review is twofold: i) providing an overview of recent applied and fundamental studies investigating the effects of MI practice on motor learning, and ii) detangling applied and fundamental findings in support of a sleep contribution to motor consolidation after MI practice. We conclude with an integrative approach of online and offline learning resulting from intense MI practice in healthy participants, and underline research avenues in the motor learning/clinical domains.